ADP receptors of platelets and their inhibition - Gachet, C (Thrombosis and haemostasis, 2001)
ADP plays a crucial role in haemostasis and thrombosis and its receptors are potential targets for antithrombotic drugs. Two G-protein coupled P2 receptors contribute to platelet aggregation: the P2Y1 receptor initiates aggregation through mobilisation of calcium stores, while the more recently identified P2Y12 receptor coupled to adenylyl cyclase inhibition is essential for a full aggregation response to ADP and the stabilisation of aggregates. The latter is defective in certain patients with a selective congenital deficiency of aggregation to ADP. It is also the target of the antithrombotic drug clopidogrel and of ATP analogues and other compounds currently under evaluation. In addition, the P2X1 ionotropic receptor is present in platelets but its role is not yet completely known. Studies in P2Y1 knock-out mice and experimental thrombosis models using selective P2Y1 antagonists have shown that the P2Y1 receptor, like the P2Y12 receptor, is a potential target for new antithrombotic drugs.